Structure and magnetic properties of titanium nickelide nanoparticles synthesized by pulsed laser ablation method - Drozdova, Anna K.; Cherepanov, Victor N.; Svetlichnyi, Valerii A.; Kveglis, Lyudmila I.; Volochaev, Mikhail N.; Velikanov, Dmitry A. (Journal of Physics: Conference Series)
We have successfully synthesized magnetic titanium nickelide nanoparticles with equiatomic composition by pulsed laser ablation method. Using transmission electron microscopy and microanalysis was revealed that particles represent the homogeneous conglomerates containing identical amount of Ni and Ti atoms. The magnetization value of nanoparticles was estimated.